2004
DOI: 10.1117/1.1802191
|View full text |Cite
|
Sign up to set email alerts
|

Elastic scattering spectroscopy for intraoperative determination of sentinel lymph node status in the breast

Abstract: The ability to provide the best treatment for breast cancer depends on establishing whether or not the cancer has spread to the lymph nodes under the arm. Conventional assessment requires tissue removal, preparation, and expert microscopic interpretation. In this study, elastic scattering spectroscopy (ESS) is used to interrogate excised nodes with pulsed broadband illumination and collection of the backscattered light. Multiple spectra are taken from 139 excised nodes (53 containing cancer) in 68 patients, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
54
0

Year Published

2004
2004
2017
2017

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 56 publications
(56 citation statements)
references
References 23 publications
2
54
0
Order By: Relevance
“…For sentinel nodes, more recently we reported on the next phase of the study, in which a larger dataset and new statistical methods were used. 44 From patients with breast cancer undergoing either sentinel node biopsy or axillary node clearance, sentinel nodes were identified using the combination technique of pre-operative lymphoscintigraphy using Tc 99 labeled albumin colloid, intra-operative blue dye injection and gamma probe guided detection. All removed nodes were bivalved, and spectra were taken from several locations on the cut surfaces of both halves with the small fiber probe in gentle contact with the node.…”
Section: Elastic Scattering Spectroscopymentioning
confidence: 99%
“…For sentinel nodes, more recently we reported on the next phase of the study, in which a larger dataset and new statistical methods were used. 44 From patients with breast cancer undergoing either sentinel node biopsy or axillary node clearance, sentinel nodes were identified using the combination technique of pre-operative lymphoscintigraphy using Tc 99 labeled albumin colloid, intra-operative blue dye injection and gamma probe guided detection. All removed nodes were bivalved, and spectra were taken from several locations on the cut surfaces of both halves with the small fiber probe in gentle contact with the node.…”
Section: Elastic Scattering Spectroscopymentioning
confidence: 99%
“…More advanced fibre optic probes for PLSS made use of gradient-index (GRIN) lens to implement depth selective measurement from a range of near surface depths (100-200 mm) to interrogate blood supply [66,67]. A great number of translational studies for diagnosis of breast cancer [68], prostate cancer [69], intraoperative determination of sentinel lymph node status in the breast [70], colonic lesions [71], oral premalignancy [72], high grade dysplasia and cancer in Barrett's oesophagus [73,74], cervix neoplasia [75,76], investigation of the nature of aceto-whitening in cervix cancer inspection [77][78][79][80][81][82], gold nanoparticle sizing [83], and monitoring apoptosis in cell cultures [84][85][86] have demonstrated that LSS provides a promising solution for cell culture monitoring, tissue surveillance and biopsy guidance in a relatively simple and cost effective configuration.…”
Section: Polarized Light and Biological Tissuementioning
confidence: 99%
“…[21][22][23][24] Recently, Johnson et al reported the study of spectral reflectance data, between 340 and 900 nm, acquired from 139 cancerous and normal sentinel nodes removed from 68 patients with breast cancers. [25] Statistical analysis of the spectral data yielded scores for discriminating different types of nodes with sensitivity and specificity comparable to those of frozen section histology.…”
Section: Spectroscopy Measurementsmentioning
confidence: 99%